Research on the performance evaluation model of national key special projects of blood center - HOU Wei (Zhongguo shuxue zazhi)
[Objective] To establish performance evaluation indicators and provide a scientific and reliable method for the performance evaluation for national key special projects of blood center. [Methods] Through literature review and Delphi method, the evaluation indicators for the national key special project performance of blood center were established. By sending indicator questionnaires to experts, the analytic hierarchy process was employed to determine the weights of each indicator. [Results] A total of 3 first-level evaluation indicators and 12 second-level evaluation indicators were established. The weights of the three first-level indicators of budget preparation, project management and project output were 0.301, 0.267 and 0.432, respectively. [Conclusion] By constructing the national key special project performance indicators of blood center, a quantifiable scientific evaluation of this process can be conducted.